Evaluating the Communicative Materials on ESP Book Entitled English for International Tourism (Universitas Negeri Semarang, 2019)
ESP is designed for a particular group of people in a specific context. The materials used are related to the learners' specialized field of study. One of the factors which is of utmost importance in language learning in general and ESP in particular is to see whether course books and other materials are useful for the purpose of the course or not. The aim of the paper is evaluating the ESP course book entitled English for International Tourism. Cunningsworth’s (1984) checklist is used to evaluate this book. Instead of the authors’ claim this book is communicative, the evaluation result shows that the exercises within the book mainly use drilling task which means it is more structural rather than communicative.